Face-Threatening Acts Performed by Characters in the “Darkest Hour” Movie - Kristian Bayu Cahyadi; I Gst. Ayu Gde Sosiowati; Putu Lirishati Soethama (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2023)
Face-threatening Acts or FTAs are an interesting phenomenon within the linguistic branch of Pragmatics to study and investigate. It involves not only acts that threaten interlocutors but also strategies for doing these acts. Subsequently, this study focused on the FTAs phenomenon, specifically occurred in the movie, Darkest Hour, a movie revolving around Winston Churchill’s reign as the UK’s Prime Minister. This study aimed to find out FTAs performed by the characters and how the characters attempt to either reduce it or not. Consequently, the data were obtained from the movie, Darkest Hour. This study used Qualitative and Descriptive methods to analyze the FTAs phenomenon in line with Brown and Levinson’s (1987) initiated theory. This study would attempt to identify what FTAs occur in the movie and determine what strategy is being used at the same time. Ultimately, this study found cases of FTA towards the hearer’s positive face (i.e., complaints, criticism, reprimands, non-cooperation, insult, expression of violent emotion, raising dangerously emotional topics, accusation, disapproval, disagreement, irreverence.) more frequent than the negative counterpart (i.e., order, suggestion, advice, warning, request, threat, anger, and reminder). In addition, the characters tend to perform those FTAs directly and without minimization. Based on those findings, the FTA phenomenon in this movie might occurred due to the character’s persistence in holding and imposing their virtues on others.